Effect of Bauhinia forficata extract in diabetic pregnant rats: maternal repercussions - Volpato, Gustavo Tadeu [UNESP]; Volpato, G. T.; Calderon, Iracema de Mattos Paranhos [UNESP]; Aguilar, R.; Rudge, Marilza Vieira Cunha [UNESP] (Urban & Fischer Verlag, 2004)
Bauhinia forficata, commonly known as paw-of-cow, is widely used in Brazil folk medicine for the treatment of Diabetes mellitus. The purposes of present study were to determine the repercussions of diabetes on the defense system against oxidative stress in pregnant female rats and to characterize the influence of the treatment with Bauhinia forficata extract on the antioxidant system, glycemic control, hepatic glycogen, cholesterol, triglycerides, total proteins and lipids. Virgin female Wistar rats were injected with 40 mg/kg streptozotocin (STZ) before mating. Oral administration of an aqueous extract of Bauhinia forficata leaves was given to non-diabetic and diabetic pregnant rats in 3 doses: 500 mg/kg from 0 to 4(th) day of pregnancy, 600 mg/kg from 5(th) to 14(th) day and 1000 mg/kg from 15(th) to 20(th) day. All the females were killed on the day 21 of pregnancy. A maternal blood sample was collected by venous puncture and the maternal liver was removed for biochemical measurement. The diabetic pregnant rats presented hyperglycemia, hyperlipemia, bypertriglyceridemia, hypercholesterolemia, hyperuricemia, decreased determinations of reduced glutathione (GSH) and superoxide dismutase (SOD). Treatment with B. forficata extract did not interfere in the albumin, total protein and lipid, triglyceride, cholesterol and SOD determinations. Increased hepatic glycogen, decreased uric acid concentration and increased GSH activity was observed. This last fact suggests that the plant may have some action on antioxidant defense system. However, the demonstration of the active component present in B. forficata responsible for its antioxidant effect and the increase in hepatic glycogen deserve further investigation.
Keywords: Bauhinia forficata; antioxidant system; medicinal plant; diabetes; pregnancy; oxidative stress